Reflecting on the Germanwings Disaster: A Systematic Review of Depression and Suicide in Commercial Airline Pilots - Pasha, Terouz; Stokes, Paul R. A. (Frontiers in Psychiatry, 2018)
Background: The 2015 Germanwings Flight 9525 disaster, in which 150 people were killed after the co-pilot may have intentionally crashed the plane in a suicide attempt, highlights the importance of better understanding the mental health of commercial airline pilots. However, there have been few systematic reviews investigating the topic of mental health in commercial aviation. This systematic review aims to identify the types and prevalence of mental health disorders that commercial airline pilots experience with a focus on mood disorders and suicide risk. Methods: A systematic literature search was performed using PubMed, EMBASE and PsycINFO databases. Eligible studies were assessed and data was extracted and analysed. Results: studies were identified. The prevalence of depression experienced by commercial airline pilots in this review ranged from 1.9-12.6%. Factors that negatively impacted the mental health of 20 pilots included substance abuse, experiencing verbal or sexual abuse, disruption in sleep circadian rhythms and fatigue. Discussion: This systematic review identifies that commercial airline pilots may experience depression at least as frequently as the general population. Commercial airline pilots experience occupational stressors such as disrupted circadian rhythms and fatigue which may increase risks of developing mood disorders. Most studies identified in this review were cross-sectional in nature with substantial limitations. There is a clear need for further higher quality longitudinal studies to better understand the mental health of commercial airline pilots.